The Natuurkundige Commissie in the Netherlands Indies (1820-1850) - Wingerden, Pieter van, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
The Natuurkundige Commissie in the Netherlands Indies was one of the largest state-sponsored colonial collecting endeavours of the early nineteenth-century world. As a result, the newly founded 's Rijks Museum van Natuurlijke Historie (present-day Naturalis Biodiversity Center in Leiden) was filled with countless specimens. The Commissie consisted of thirty naturalists and was active for thirty years (1820-1850). This book shows how its stakeholders had different objectives that evolved over time: what started as a collection vehicle to showcase the 'glory' of the Dutch colonial empire became a useful surveying tool for the Indies government. This volume is the first detailed study of the Commissie in English. It tells the story of naturalists from the Netherlands, France, and German-speaking lands and of countless indigenous people working alongside the Commissie as knowledge brokers, hunters, preparators, and porters. This long overlooked indigenous contribution to European knowledge was both substantial and fundamental.